Nyadranan, Bentuk Akulturasi Islam Dengan Budaya Jawa (Fenomena Sosial Keagamaan Nyadranan Di Daerah Baron Kabupaten Nganjuk) - Nizarudin Wajdi, Muh. Barid (STAI Miftahul Ula Nganjuk, 2017)
Nyadran is the symbolic of a relationship among ancestors, nature and each other. It is a ritual pattern that contains local culture and Islamic values. Thus, it is not surprising that the implementation of Nyadran still has to do with Buddhist culture and Hindu-Animism which was later assimilated by Islamic values by Wali Songo. In addition, this study would investigate how the relationship between Nyadranan and Islamic values. A qualitative research approach was applied to answer research questions. This study was conducted in Baron, Nganjuk City. Observation and in-depth interviews were applied to collect data. This result indicated that it was a very strong relationship. Nyadran was the social expression of community, solidarity and togetherness being the main pattern of this tradition. This phrase would ultimately result in a vertical-horizontal relationship more closely. In this context, then Nyadran would be able to improve the pattern of the relationship between God and society, and thus eventually would show the development between cultures and traditions that had evolved into more colorful.